Pengaruh Profitabilitas, Likuiditas Dan Ukuran Perusahaan Terhadap Kebijakan Dividen Perusahaan Manufaktur Periode 2016-2018 - Ega Aditya; Ronny Malavia Mardani; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract  This study aims to determine and analyze the effect of profitability, liquidity and company size on manufacturing companies in the 2016-2018 period. This Type of research is Explanatory Research. Explanatory Research is an investigation that is intended to explain the relationship between variables through hypothesis testing. In this study using independent variables (return on investmen (ROI), current ratio (CR), firm size and the dependent variable dividend payout ratio (DPR). The data analysis technique used is panel data regression analysis, t test. The population in this study is manufacturing companies in the consumer goods industry sector, while the sample used is 47 companies in the consumer goods industry sector. This manufacturing company data is used to determine whether each variable influences the dividend policy. Data were analyzed descrptively quantitatively. The results obtained from this study are (1) Return On Investmen (ROI) negative effect on Dividend Payout Ratio (DPR). (2) Current Ratio (CR) negative effect on Dividend Payout Ratio (DPR). (3) Firm Size positive effect on Dividend Payout Ratio (DPR). Keywords : Return On Investmen, Current Ratio, Firm Size, Dividend Payout Ratio